Step in Time: Biomineralisation of Bivalve’s Shell - Louis, Victoria; Besseau, Laurence; Lartaud, Franck (Frontiers in Marine Science, 2022)
Biomineralisation process which is the induction of the precipitation of a mineral by an organism, generates hard tissues such as bones, teeth, otoliths and shells. Biomineralisation rate is not constant over time. This is likely due to variations of environmental and/or physiological conditions, leading to the formation of growth increments or rings. For bivalves, increments are considered as the unit of time recorded in shells. Therefore, shells are used as biological archives of (paleo)environmental and (paleo)climatic conditions. However, the environmental drivers leading to the periodic formation of increments are still poorly understood. Tackling the question of the integration of the environment by the organism is challenging : is there a direct effect of the environmental variability on bivalve shell biomineralisation? Or is biomineralisation controlled by a biological clock? In this review, the different temporal units observed in bivalve shells and the possible regulatory processes are explored and some research trajectories are suggested.